Performance assessment of a novel pyramid photobioreactor for cultivation of microalgae using external and internal light sources - Khoobkar, Zahra (Array, 2019)
The cultivation of Chlorella sp., the most abundant microalga in the Persian Gulf, took place in a novel pyramid photobioreactor (PBR), a modified version of plate PBR, consisting of four completely separate equal-volume chambers. In this study we used two light sources incident in each chamber: light-emitting diode (LED) at various wavelengths (red, white and blue) of 108 µmol/(m2·s) photosynthetic photon flux density as internal lighting, and the same photon flux density for external white lighting. PBR served to study the effects of light sources on chlorophyll a production, maximum specific growth rate (µmax), biomass productivity rate (rp) and photon performance. The results showed that the highest chlorophyll a production was obtained under red LED illumination. The highest values for rp, µmax and photon performance were obtained under white light.